2019
DOI: 10.1021/acs.inorgchem.9b03006
|View full text |Cite
|
Sign up to set email alerts
|

The Fluorine Effect in Zwitterionic Half-Sandwich Iridium(III) Anticancer Complexes

Abstract: The rational design by the introduction of fluorine into a compound has achieved success in the development of organic anticancer drugs. However, the fluorine effect in metal-based anticancer complexes has rarely been reported. In this contribution, we report the synthesis, characterization, chemical reactivity, and biological activity of a series of half-sandwich zwitterionic iridium(III) complexes containing different substituents in the η 5 -Cp R ring. The molecular structures for complexes Ir1−Ir4 and Ir7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 48 publications
(73 reference statements)
0
24
1
Order By: Relevance
“…Pt drugs have achieved great success in the field of cancer chemotherapy. However, the side effect of these Pt drugs has led chemotherapy research toward alternate anticancer agents such as Ru, Rh, Ir, and Os complexes. In particular, organometallic half-sandwich complexes of some platinum group metals (Ru, Rh, Ir, and Os) have received considerable attention due to their easy tunable structure, high potency toward cancer cells, and specific mechanism of actions (MoAs). Generally, the central metals of these 18-electron complexes [(η 5 -Cp)/(η 6 -arene)­M­(XY)­Cl] 0/+ (Cp = functionalized cyclopentadienyl; M = Ru, Rh, Ir, Os; XY = bidentate ligands) have adopted six-coordinated geometry, where the chlorine atom, the bidentate ligand XY, and η 5 -Cp/η 6 -arene occupy one coordination site, two coordination sites, and three coordination sites, respectively (Scheme , I ). It should be noted that hydrolysis of M–Cl bonds, i.e., Cl – /H 2 O exchange, usually represents an activation step for these 18-electron complexes, since M–H 2 O aqua were usually more reactive than the corresponding chloride analogues .…”
Section: Introductionmentioning
confidence: 82%
“…Pt drugs have achieved great success in the field of cancer chemotherapy. However, the side effect of these Pt drugs has led chemotherapy research toward alternate anticancer agents such as Ru, Rh, Ir, and Os complexes. In particular, organometallic half-sandwich complexes of some platinum group metals (Ru, Rh, Ir, and Os) have received considerable attention due to their easy tunable structure, high potency toward cancer cells, and specific mechanism of actions (MoAs). Generally, the central metals of these 18-electron complexes [(η 5 -Cp)/(η 6 -arene)­M­(XY)­Cl] 0/+ (Cp = functionalized cyclopentadienyl; M = Ru, Rh, Ir, Os; XY = bidentate ligands) have adopted six-coordinated geometry, where the chlorine atom, the bidentate ligand XY, and η 5 -Cp/η 6 -arene occupy one coordination site, two coordination sites, and three coordination sites, respectively (Scheme , I ). It should be noted that hydrolysis of M–Cl bonds, i.e., Cl – /H 2 O exchange, usually represents an activation step for these 18-electron complexes, since M–H 2 O aqua were usually more reactive than the corresponding chloride analogues .…”
Section: Introductionmentioning
confidence: 82%
“…Platinum metal-based anticancer drugs have achieved great success in the treatment of various tumors. However, side effects and drug resistance have stimulated exploration of alternative metal complexes. Among these complexes, half-sandwich organometallic platinum group metal-based (ruthenium, iridium, rhodium, and osmium) complexes with the piano-stool configuration have been well studied as anticancer agents. These complexes have shown promising anticancer activity and some different mechanisms of action (MoAs) with platinum drugs. For example, Sadler and co-workers reported that the high-potency phenylpyridine iridium­(III) complexes (Scheme , I ) induced a significant increase in reactive oxygen species (ROS) in cancer cells, which involved catalytic hydride transfer from the coenzyme NADH to oxygen to generate the ROS hydrogen peroxide (H 2 O 2 ). , Our group has also found that the cationic half-sandwich pyridyl–imine iridium­(III) and ruthenium­(II) complexes could produce significant levels of ROS, disrupt the mitochondrial membrane, and show potent anticancer activity toward A549 cancer cells (Scheme , II and III ). , Interestingly, some ruthenium­(II) complexes achieved good selectivity toward cancer cells and normal cells. , More recently, we further demonstrated that the metal variation in the zwitterionic pyridyl–imine half-sandwich complexes and the introduction of fluorinated substituents resulted in a significant increase in the anticancer activity (Scheme , IV ). Notably, the coordination fashion of the abovementioned pyridyl–imine half-sandwich iridium­(III) complexes was imine-metal. Along this line, we became interested in expanding our investigation to the synthesis and biological evaluation of the corresponding amine–metal and amido–metal complexes (Scheme ).…”
Section: Introductionmentioning
confidence: 96%
“…While considerable research has been made on nonplatinum drugs based on titanium, iron, gallium, tin, iridium, and gold, the ruthenium , -based drugs have received special attention in cancer treatment, as they are not only less toxic , with an attractive redox kinetics property but also demonstrate in vivo performances that are quite similar to those of platinum-based drugs . In addition, ruthenium faithfully mimics iron in its interaction with proteins, which leads to a selective communication with cancer cells via two favorable oxidation states (II) and (III).…”
Section: Introductionmentioning
confidence: 99%